A dimensão formativa como mobilizadora da ação supervisora - Bandler, Paula Cristina Castro Pinheiro (2022)
The historical course of the position of school supervisor reveals that its performance has been changing since its constitution. We have observed a shift from a supervisory and administrative perspective to one that emphasizes the formative and collaborative dimension. Due to the influence of this new scenario, this research intends to identify and analyze what drives the school supervisor to perform a pedagogical oriented work in his supervisory action. The inspiration for this theme can also be found in the researcher's professional background, which includes her involvement in training processes and the partnership experience she had with school supervision when she had worked as a pedagogical coordinator. The theoretical support was based mainly on the authors Alarcão (2002, 2013, 2014), Alarcão e Canha (2013), Alarcão e Tavares (2018), Oliveira-Formosinho (2002, 2009), Rangel (1997, 2008, 2013), Salmaso e Almeida (2017) and Silva Júnior (1997). The theoretical-methodological path was based on a qualitative research approach and developed through semi-structured interviews (LÜDKE; ANDRÉ, 2018) conducted with eight school supervisors from São Mateus Regional Board of Education, as well as documentary analysis. The data analysis turned to the Prose Analysis methodology (ANDRÉ, 1983) and gave rise to four analytical categories. The data made it possible to identify that the supervisors invest in a dialogical, collaborative and partnership work and that the conception of their role was built prioritizing the formative and pedagogical dimension as the center of all supervisory action. We found that the supervisors wish to be participants in the construction of the educational policies of the Municipal Education Network of São Paulo (RME-SP), wish to participate in training processes in partnership with the University and seek to establish, in their work routine, collective groups of study and reflection. Considering these findings make us suggest ways such as the creation of collaborative and reflective groups in the work context, because they can favor the partnership with the University and improve the knowledge and supervisory practices